Growth Motivation For UK Small Business Owners: Understanding Their Limiting Factors - Preece, P M (2011)
The purpose of this report is to understand, from an owners’ perspective, the limiting factors regarding growth in Small and Medium Enterprises (SMEs). Theoretically we discuss attitudes towards growth, the value of available resources, understanding the importance of business timescales, the motivations of the owner, ambitions for the business and reactions to uncertainty. The major findings are summarized: